Analisis Akun Berpengaruh pada Tagar #MencuriRadenSaleh di Twitter dengan Social Network Analysis - Evangs Mailoa; Gilang Agung Saputra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Twitter users come from various backgrounds and interests, ranging from just looking for entertainment, information, business needs, or discussion. Many discussion topics can be found on Twitter especially using Hashtags. A topic will form communication with other accounts, one of the hashtags is the hashtag #MencuriRadenSaleh, the hashtag comes from the title of the film Mencuri Raden Saleh which was released on August 25, 2022. This study analyzes the communication network formed by the hashtag #MencuriRadenSaleh using the Social method Network Analysis to find influential accounts in the communication network that is formed, the analysis uses the calculation of degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality. The data is in the form of tweets containing the hashtag #MencuriRadenSaleh taken from 15 August 2022 to 25 August 2022 with a total of 9041 nodes and 6064 edges. The results of the research conducted show that the accounts @umayshhhhb, @iqbaal, and @mrs_film are influential accounts in the formation of communication networks and information dissemination with the hashtag #MencuriRadenSaleh, the accounts @umayshhhhb and @iqbaal is owned by the actor Mencuri Raden Saleh, and @mrs_film is the official account of the film.